The Revaluation of Plant-Derived Terpenes to Fight Antibiotic-Resistant Infections - Cappiello, Floriana (Antibiotics (Basel), 2020)
The discovery of antibiotics has revolutionized the medicine and treatment of microbial infections. However, the current scenario has highlighted the difficulties in marketing new antibiotics and an exponential increase in the appearance of resistant strains. On the other hand, research in the field of drug-discovery has revaluated the potential of natural products as a unique source for new biologically active molecules and scaffolds for the medicinal chemistry. In this review, we first contextualized the worldwide problem of antibiotic resistance and the importance that natural products of plant origin acquire as a source of new lead compounds. We then focused on terpenes and their potential development as antimicrobials, highlighting those studies that showed an activity against conventional antibiotic-resistant strains.